Issues of context, capacity and scale: Essential conditions and missing links for a sustainable blue economy. Issue 130 (April 2022) - Niner, Holly J.; Barut, Noel C.; Baum, Tom; Diz, Daniela; Laínez del Pozo, Daniela; Laing, Stuart; Lancaster, Alana Malinde S.N.; McQuaid, Kirsty A.; Mendo, Tania; Morgera, Elisa; Maharaj, Payal N.; Okafor-Yarwood, Ifesinachi; et al.
Abstract: The blue economy has roots in the international arena of sustainable development and sets out to unlock opportunities for economy and society whilst protecting and enhancing marine environments. To date there has been no analysis of how this overarching intention for sustainability has influenced the rapid development of blue economy policies at national and regional scales. In this article, we analyse the synergies and conflicts between blue economy policies from a diversity of national and regional policies and the UN Sustainable Development Goals. We show that to maintain critical alignment with targets for sustainability, place-based contextual development of blue economies that meet the needs of all actors is necessary. These needs relate to ensuring resilience against future environmental and political shocks, the maintenance of the ecological basis for thriving blue economies, and capacity development at all levels to support effective and equitable governance. Results indicate that co-production will be important to achieve sustainable blue economies. Highlights: Blue economies are not inherently aligned with the sustainable development goals. Translation of international aims of sustainability to local level is challenging. Place-based contextual development of blue economies is needed for sustainability. Policies weakly support capacity development to address complex societal issues. coproduction and capacity development is needed for sustainable blue economies.